Curcumin effects on glycaemic indices, lipid profile, blood pressure, inflammatory markers and anthropometric measurements of non-alcoholic fatty liver disease patients: A systematic review and meta-analysis of randomized clinical trials - Armin Ebrahimzadeh; Shokouh Mohseni; Mohammad Safargar; Abbas Mohtashamian; Sara Niknam; Mohammadreza Bakhoda; Sanaz Afshari; Amirhossein Jafari; Anahita Ebrahimzadeh; Sara Fooladshekan; Alireza Mohtashami; Gordon A. Ferns; et al. (Elsevier, 2024)
Objectives: Curcumin has antioxidant properties and has been proposed as a potential treatment for NAFLD. The aim of current systematic review and meta-analysis was to evaluate previous findings for the effect of curcumin supplementation on glycaemic indices, lipid profile, blood pressure, inflammatory markers, and anthropometric measurements of NAFLD patients. Methods: Relevant studies published up to January 2024 were searched systematically using the following databases: PubMed, SCOPUS, WOS, Science Direct, Ovid and Cochrane. The systematic review and meta-analysis were conducted according to the 2020 PRISMA guidelines. The quality of the papers was assessed the using the Joanna Briggs Institute (JBI) Critical Appraisal Checklist. Pooled effect sizes were calculated using a random-effects model and reported as the WMD and 95% CI. Also, subgroup analyses were done to find probable sources of heterogeneity among studies. Results: Out of 21010 records initially identified, 21 eligible RCTs were selected for inclusion in a meta-analysis. Overall, 1191 participants of both genders, 600 in the intervention and 591 in the control group with NAFLD were included. There are several limitations in the studies that were included, for instance, the results are weakened substantially by potential bias or failure to account for potential adulteration (with pharmaceuticals) or contamination (with other herbs) of the curcumin supplements that were tested. However, previous studies have reported curcumin to be a safe complementary therapy for several conditions. Our study indicated that curcumin supplementation in doses of 50−3000 mg/day was associated with significant change in FBG [WMD: −2.83; 95% CI: −4.61, −1.06), I2 = 51.3%], HOMA-IR [WMD: −0.52; 95% CI: −0.84, −0.20), I2= 82.8%], TG [WMD: −10.31; 95% CI: −20.00, −0.61), I2 = 84.5%], TC [WMD: −11.81; 95% CI: −19.65, −3.96), I2 = 94.6%], LDL [WMD: −8.01; 95% CI: −15.79, −0.24), I2 = 96.1%], weight [WMD: −0.81; 95% CI: −1.28, −0.35), I2= 0.0%] and BMI [WMD: −0.35; 95% CI: −0.57, −0.13), I2= 0.0%] in adults with NAFLD. There was no significant change in HbA1C, plasma insulin, QUICKI, HDL, SBP, DBP, CRP, TNF-α and WC after curcumin therapy. Subgroup analysis suggested a significant changes in serum FBG, TG, SBP, WC in RCTs for intervention durations of ≥ 8 weeks, and SBP, TG, LDL, HDL, BMI, WC in RCTs with sample size > 55 participants. Conclusion: Curcumin supplementation in doses of 50−3000 mg/day over 8-12 weeks was associated with significant reductions in levels of FBG, HOMA-IR, TG, TC, LDL, weight and BMI in patients with NAFLD. Previous studies have reported curcumin as a safe complementary therapy for several diseases. We would suggest that should curcumin supplements be used clinically in specific conditions, it should be used with caution. Also, difference in grades of NAFLD may effect the evaluated outcomes, so it is suggested that future studies be conducted with an analyses on subgroups according to their NAFLD grade. Furthermore, because of the failure to conduct independent biochemical assessment of the turmeric/curcumin product used in most studies as well as potential sources of bias, results should be interpreted with caution.